Defense Effect of Ganoderma lucidum Against Zinc Oxide Nanoparticles Induced Nephrotoxicity - Ozdan Akram Ghareeb (Genius Journals, 2022)
Zinc oxide nanoparticles are growing in use in many fields, especially cosmetics. However, its potency effects on renal tissue are still predominately unknown. The purpose of this study is to confirm the toxicity of these particles on the kidneys of experimental rats and to assess the role of Ganoderma lucidum (GL) against ZnONPsinduced nephrotoxicity. This study was conducted on thirty male rats divided into three experimental groups (each group includes ten) as follows: CON group without any treatment, ZnONPs group in which rats were intoxicated with zinc oxide nanoparticles orally, and ZnONPs+ GL group which co-received GL poisoned rats. After nephrotoxicity was evaluated, the results showed a significant increase in serum renal function biomarkers including BUN, CR, and URIC in ZnONPs -treated rats compared to CON rats. Moreover, ZnONPs led to lower levels of GSH and SOD with higher levels of MDA in kidney tissues. Combined administration of GL has shown an improved effect against nephrotoxicity, as it has the role of modulating the level of parameters of renal function and oxidative stress induced by ZnONPs. It is suggested that it is desirable to employ GL as a salutary reno-defense nutrient against ZnONPs -induced toxicity
Keywords: Nephrotoxicity; biochemical markers; oxidative stress